2005
DOI: 10.1021/es050087u
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Inorganic and Organic Ligands onto Hydrous Aluminum Oxide:  Evaluation of Surface Charge and the Impacts on Particle and NOM Removal during Water Treatment

Abstract: The variable removal from solution of sulfate, orthophosphate, fluoride, five simple organic acids, and natural organic matterfromtwo sources by adsorption on aluminum hydroxide was examined to assess their potential influence on coagulation during drinking water treatment. Measurements of electrophoretic mobility were conducted with adsorption studies to provide means of evaluating the impact of the adsorption of these anions on the removal of particulate material during coagulation at water treatment facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 24 publications
4
38
1
Order By: Relevance
“…Our previous study also indicated the adverse effect of fluoride on the coagulation behavior of aluminum chloride (AlCl 3 ) towards kaolin suspensions, and the formation of Al-F complexes at high fluoride levels plays an important role [18]. Besides the formation of Al-F complexes, the attachment of fluoride onto Al hydroxide decreased the surface charge and particles stability [19], and this effect was assumedly to inhibit the removal of negatively-charged arsenate [As(V)]. Additionally, the competitive effect between As(V) and F occurs to affect their adsorption onto AlOxHy, and this adverse effect may be remarkably alleviated by introducing iron oxides to AlOxHy [6].…”
Section: Introductionmentioning
confidence: 96%
“…Our previous study also indicated the adverse effect of fluoride on the coagulation behavior of aluminum chloride (AlCl 3 ) towards kaolin suspensions, and the formation of Al-F complexes at high fluoride levels plays an important role [18]. Besides the formation of Al-F complexes, the attachment of fluoride onto Al hydroxide decreased the surface charge and particles stability [19], and this effect was assumedly to inhibit the removal of negatively-charged arsenate [As(V)]. Additionally, the competitive effect between As(V) and F occurs to affect their adsorption onto AlOxHy, and this adverse effect may be remarkably alleviated by introducing iron oxides to AlOxHy [6].…”
Section: Introductionmentioning
confidence: 96%
“…Several methods have been applied to remove excessive fluoride from aqueous environments, such as adsorption [2,[8][9][10], precipitation [6], ion-exchange [11], electrodialysis [12] and electrochemical methods [13]. Among them, precipitation and adsorption are two most important techniques used for water defluoridation.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of fluoride onto hydrous aluminum oxides via ligand exchange, as indicated by Eq. (1), cannot contribute to ζ-potential reversal, although it did decrease the ζ-potential to some extent (Pommerenk and Schafran, 2005). In this study, fluoride significantly lowered the ζ-potential and the reversal of the ζ-potential to negative values was observed.…”
Section: Modeling Methodsmentioning
confidence: 39%
“…Besides Al-F complex formation, the adsorption of fluoride onto Al hydro (oxide) also plays a role. Pommerenk and Schafran (2005) indicated that the attachment of fluoride on hydrous aluminum oxide decreased its surface charge and adversely affected the removal of natural organic matter (NOM) accordingly (Pommerenk and Schafran, 2005). Furthermore, aluminum oxide tends to dissolve in the acidic pH range.…”
Section: Introductionmentioning
confidence: 99%